Macular morphology and visual acuity after macular hole surgery with or without internal limiting membrane peeling. Issue 1 (18th August 2009) - Christensen, U C; Krøyer, K; Sander, B; Jorgensen, T M; Larsen, M; la Cour, M
Abstract : Aim: To examine postoperative macular morphology and visual outcome after 12 months in relation to internal limiting membrane (ILM) peeling versus no peeling, indocyanine green (ICG) staining and re-operation in eyes that achieved macular hole closure after surgery. Methods: Seventy-four eyes with closed stage 2 or 3 macular holes were recruited from a randomised clinical trial comparing: (1) vitrectomy without ILM peeling; (2) vitrectomy with 0.05% isotonic ICG-assisted ILM peeling; and (3) vitrectomy with 0.15% trypan blue-assisted ILM peeling. Contrast-enhanced Stratus optical coherence tomography was used to assess central foveal thickness, central photoreceptor layer thickness (CPRT), central photoreceptor layer discontinuity (PRD) and relative reflectivity of the outer nuclear layer. Outcomes were correlated with best corrected visual acuity (BCVA) 12 months after surgery. Results: BCVA was correlated with CPRT and PRD. Regression analysis and receiver operating characteristics curve analysis showed that CPRT >33 μm (OR 12.5) and PRD <177 μm (OR 9.86) were highly predictive for regaining reading vision (⩾69 Early Treatment of Diabetic Retinopathy Study letters) 12 months after surgery. No significant difference was found in postoperative macular morphology between subgroups. Conclusions: Poor vision after 12 months despite macular hole closure was associated with attenuation and disruption of the foveolar photoreceptor matrix. The extent of attenuation and disruption was independent of peeling and staining. Trial registration number: NCT00302328